The Concept of Information Poverty and How to Measure it in the Latin American Context - Gover Barja; Björn-Sören Gigler (Digital Poverty: Latin American and Caribbean Perspectives, 2007)
The construction of the information society must be complemented with pro poor vision and policies. For this reason, this paper defines the concept of information and communication poverty, introduces the criteria of poverty line location for its identification, and suggests computation for the economic cost of reaching such a line for its aggregate measurement. In this process, the structural and technological restrictions faced by a society are acknowledged, and the way they affect and are affected by the concept of information and communication poverty is discussed. This research study examines these issues conceptually, in order to contribute to the study regarding magnitude, depth and characteristics of information and communication poverty, as well as to identify some of its implications for drafting public policies.
Keywords: 330; Information and communication poverty; Poverty line location; Economic cost analysis